Validation of a French-Canadian Version of the Pain Disability Index. (2008) - Gauthier, Nathalie; Thibault, Pascal; Adams, Heather; Sullivan, Michael JL
Abstract : OBJECTIVE: To examine the psychometric properties of the Index de l'incapacité reliée à la douleur, a French-Canadian version of the Pain Disability Index (PDI). METHODS: A total of 176 chronic pain patients (94 women, 82 men) completed the French-Canadian version of the PDI (PDI-CF), as well as other pain-related measures. A subset of 52 patients (27 women, 25 men) also completed a lifting task designed to assess physical tolerance and pain behaviour. RESULTS: Confirmatory factor analysis of the PDI-CF supported the two-factor structure of the original PDI. Reliability analyses revealed that the PDI-CF total score had a high degree of internal consistency, comparable with the original PDI. The PDI-CF total score was significantly correlated with self-reported pain, pain catastrophizing, depressive symptoms, fear of movement or (re)injury, lift duration and pain behaviours. CONCLUSIONS: The results suggest that the PDI-CF is a reliable and valid measure of self-reported disability that is psychometrically similar to the original scale.